Numbers 4:20 and Non-Priestly Viewing of the Holy Vessels in the Second Temple Period - Orian, Matan (2024)
In discussing the dismantling and transport of the tabernacle and its furnishings, Numbers 4:20 prohibits any viewing of the “holy,” except by Aaron, the priest, and his sons. Philo of Alexandria, as well as several modern scholars, read this as a prohibition on any non-priestly viewing of the sacred, Jewish cultic vessels, including the menorah, the shewbread table and the incense altar. Accordingly, a dominant view in research holds that during the Second Temple period these cultic utensils were concealed from the sight of non-priests. However, this view partly overlooks and partly misinterprets our main source in that respect: Josephus indicates that the Jewish holy vessels were actually displayed to the Jewish crowd gathered in the temple court during the Second Temple period. This is supported by the images on certain Hasmonean coins as well as by later texts, such as P.Oxy. 840 and rabbinic literature.
Keywords: cultic images; Papyrus Oxyrhynchus 840; Josephus; Philo; holy vessels; Biblical Interpretation